Long Term Preservation of Websites - Herschung, Alexander (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
While websites are of great interest for digital archives, the digital long term preservation of websites is a huge problem. The reason is that websites consist of a large number of file formats and require today’s hardware and software environment to work properly. PABLO is a software tool that processes websites and transforms them into a dramatically simplified form that is simple enough for digital archiving and exhaustive enough to preserve the websites content and appearance and allows users to browse the entire site like the original.
Keywords: Digital Long Term Preservation; Website Archiving